A versatilidade da Periclase (MgO) no tratamento de água residuária contendo cromo e seu reuso como pigmentos inorgânicos - Balaba, Nayara (2021)
This dissertation went aimed to synthesize of magnesium oxide (MgO), through the colloidal starch method to be used for removal chromium (III) ions of synthetic wastewater and application as synthetic inorganic pigments at commercial paint. Thus, this work was divided into 8 chapters, where chapter 4 deals with the characterization of the synthesized and commercial MgO used as reference. The synthesis of oxide was prepared for an environmentally friendly methodology from the aqueous emulsion of cassava starch and magnesium nitrate, calcined at 750 ºC. The MgO synthesized and commercial were characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM), energy dispersive X-ray fluorescence (EDXRF), Fourier transforms infrared spectroscopy (FTIR) in ATR mode, surface area analysis by B.E.T. method and thermogravimetric analysis (TG/DTG). The synthesized oxide is presented as sigle-phase periclase, while the commercial oxide also presents brucite phase. After the removal chromium (III) ions with synthesized and commercial oxide, the green pigments were obtained and the insertion of the cations led to change of the periclase phase to brucite phase. The green pigments were calcined at 1000 ºC, lead to the formation of yellowish pigments after the sintering of materials. The green and yellow pigments were characterized by XRD, SEM, EDXRF and FTIR. The samples were dispersed in commercial white paint, and used to paint gypsum blocks, simulated the wall covering. The colors were studied by colorimetric parameters by CIEL*a*b*C*h* method and electron absorption spectroscopy (UV-Vis). Leaching test was performed by immersion of the painted blocks for 24 hours and quantified by Flame Atomic Absorption Spectroscopy (FAAS), and no leaching of chromium was detected after this period for all pigments. The purpose of this work was to search for an alternative means of purification of wastewater contaminated with chromium and its reuse in the formation of synthetic inorganic pigments through an innovative synthetic route.